Communication Patterns of the Head of Religious Affairs Office (KUA) in Reducing the Divorce Rate - Basri Basri; Erman Anom (Yayasan Ilomata, 2023)
This study aims to determine the pattern of communication carried out by the Bangko District Office of Religious Affairs (KUA) in reducing the divorce rate in Bangko District, Rokan Hilir Regency, Riau Province. The research method employed is qualitative, with a case study approach. The results of this study show that the pattern of communication carried out by the Bangko District Office of Religious Affairs (KUA) in reducing the divorce rate in Bangko District uses the Lasweell model communication pattern and the stimulus-response (S-R) communication pattern. Where the Office of Religious Affairs (KUA) of Bangko Subdistrict is carrying out its activities, it always conducts communication analysis, which includes elements of effective communication and which, in the end, shows whether the response obtained from the stimulus results goes according to purpose or not. Based on the researcher's analysis, it was concluded that the pattern of communication that was carried out had not had a significant impact, meaning that it still increased the divorce rate in Bangko District. However, the pattern of communication that is carried out makes a good contribution to the husband and wife who are going to divorce in the form of consideration in making the decision to divorce.